Characterization of Sewage Sludge Ash (SSA) in Cement Mortar - Chin, Siew Choo; Doh, Shu Ing; Kusbiantoro, Andri; Yih, Kang Wong; Saffuan, Wan Ahmad (Asian Research Publishing Network (ARPN), 2016)
Sewage sludge Ash (SSA) is a waste material obtained from the incineration of waste water sludge. The SSA generated from the burning usually is disposed of to the landfill which is not the final solution. Hence an investigation was carried out to study the potential use of SSA in cement base material. The chemical mineralogical characteristic of SSA in cement mortar were examined. The percentage of SSA considered in this study was 10% replacement of the mass of cement whereas the incineration temperatures investigated was at 600° and 800°C. The test conducted in this study including X-ray Diffraction (XRD), X-ray Fluorescence (XRF) and Filed Emission Scanning Electronic Microscope (FESEM) and compressive strength test. Result show significant amount of SiO², Al²O³ and CaO was traced after the incineration process. Mortar sample with 10% replacement of 800°C burnt SSA improves the compressive strength up to 1.14% and 5.06% at the ages of 28 and 98 days, respectively. The FESEM test result show that SSA samples in 600°C exhibited needle-shape particles and a smooth structure in 800°C due to pozzolanic activity which filled the void and pores in the mortar. The bonding also provides additional strength to the mortar in which the compressive strength has increased after 28 days and 90 days